Sleeve Fuse System For Improved Steel Connection Performance - Atar, Muhammed (My University, 2025)
This study introduces an approach to improving the connection performance of steel structures by utilizing a sleeve fuse mechanism. The system introduced suggest a steel sleeve which is positioned between the end plate and the nut to modify the load path for improving the system's ductility. To validate the proposed method, experimental models from existing studies were employed, ensuring that the numerical simulations provided accurate results. A range of sleeve designs were analysed utilising a numerical FE model, confirming the system's efficacy in improving connection behaviour. The sleeve system showed notably better performance than conventional end-plate connections. The results indicate that the system increases the connection’s rotational capacity by 85%, functioning as a structural fuse under monotonic loading and enhancing both ductility and energy absorption by 90%. Additionally, the increased elongation of the bolts further contributes to the rotational capacity, providing greater stability to the frame structure. Overall, this sleeve-based system offers a promising advancement over conventional designs by boosting energy absorption and ductility, making it a robust alternative for improving connection performance.
Keywords: Steel structures; Ductility; Bolted connections; Monotonic loading; Fuse system